2008
DOI: 10.1002/bem.20382
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Thermal effects in the microwave induced unfolding of proteins observed by chaperone binding

Abstract: We study the effect of microwaves at 2,450 MHz on protein unfolding using surface plasmon resonance sensing. Our experimental method makes use of the fact that unfolding proteins tend to bind to chaperones on their unfolding pathway and this attachment is readily monitored by surface plasmon resonance. We use the protein citrate synthase (CS) for this study as it shows strong binding to the chaperone alpha crystallin when stressed by exposure to excess temperature. The results of microwave heating are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 14 publications
3
42
1
Order By: Relevance
“…Non-thermal as well as thermal effects contribute to the efficacy of microwave ablation [3]. George et al reported unfolding of enzymes caused by direct electromagnetic impacts either on protein structure or on hydration-water [33]. Furthermore, Yu and Yao reported an inhibition of DNA synthesis and proliferation arrest in rabbit lens cells, which led to apoptotic changes.…”
mentioning
confidence: 99%
“…Non-thermal as well as thermal effects contribute to the efficacy of microwave ablation [3]. George et al reported unfolding of enzymes caused by direct electromagnetic impacts either on protein structure or on hydration-water [33]. Furthermore, Yu and Yao reported an inhibition of DNA synthesis and proliferation arrest in rabbit lens cells, which led to apoptotic changes.…”
mentioning
confidence: 99%
“…The nature of the debate surrounding this interaction has often referred to the existence of so-called specific microwave (MW) effects that are nonthermal in nature (4,10,13,17,20,28,29). Much has been published supporting the notion that a range of specific MW effects exist and can be identified in terms of their manifestations on cell physiology (2,4,10,13,27,28). For example, Dreyfuss and Chipley examined the effects of MW radiation (2.45 GHz) at sublethal temperatures on the metabolic activities of a range of enzymes expressed by the bacterium Staphylococcus aureus (10).…”
mentioning
confidence: 99%
“…Low-intensity 935 MHz radiation can affect microtubule proteins and suppress cell growth. Pacini et al (40) ) for up to 100 h. However, two independent groups of investigators demonstrated the capability of lowpower UHF radiation to induce reversible changes to cell protein structure, affect beta-lactoglobulin conformational changes, and stimulate the unfolding of citrate synthase (42)(43)(44). In addition, Leszczynski et al (45) found that mobile phone radiation changes the phosphorylation status of the heat shock protein-27, one of the stress family proteins.…”
Section: Cellular Biomarkers Of Rf/mw Exposurementioning
confidence: 99%